Advanced Optical Analysis of Divergence Between the Foci of the Neodymium-Doped Yttrium Aluminum Garnet (Nd:YAG) and Aiming Beam Lasers - Averbukh, Edward; Slushetz, Yaakov; Levy, Jaime; Patal, Rani; Mandelbaum, Yaakov; Arieli, Yoel (Ophthalmology science (Online), 2024)
To evaluate the divergence between the neodymium-doped yttrium aluminum garnet (Nd:YAG) surgical laser and the aiming diode laser beams foci. Optical analysis and measurements were performed using a Volk Goldmann 3-mirror lens with a Nidek YC-1800 Nd:YAG laser apparatus. None. We used the Zemax OpticStudio program for the model of Nd:YAG treatment in a human eye. Additionally, theoretical calculations were performed. The divergence between the Nd:YAG laser focus and the intersection of the 2 aiming beams inside the eye. Focal points of the 2 laser beams converge 8 mm behind the cornea. Posterior to this point, the intersection of the diode laser aiming beams lies in front of the focal point of the Nd:YAG treatment laser, with distance between the 2 foci progressively increasing up to 305 microns at 24 mm behind the cornea. We report the degree of divergence between the 2 lasers’ focal points due to the difference in refraction between the corresponding wavelengths. These results have high practical relevance, as they provide a starting point for increasing the accuracy of Nd:YAG laser treatment, particularly when applied to the posterior segment, thereby minimizing the risk of complications. Current Nd:YAG laser devices have the built-in ability to modify the focal point of the aiming beam along the z-axis, thus providing possibility for an immediate application of our findings in clinical practice. The authors have no proprietary or commercial interest in any materials discussed in this article.